2023
DOI: 10.3390/jmse12010019
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Configuration of Hybrid Reverse Osmosis, Humidification–Dehumidification, and Solar Photovoltaic Systems: Modeling and Exergy Analysis

Ahmed E. Tourab,
Ana María Blanco-Marigorta,
Aly M. Elharidi
et al.

Abstract: The pressing demand for clean water worldwide has increased attention to developing innovative desalination processes. In this work, the second law of thermodynamics is used to examine and assess two coupled desalination systems: a separation-based reverse osmosis (RO) system and a thermal desalination-based humidification–dehumidification (HDH) system. The HDH unit configuration used here is based on the working principle of the heat pump, where the process is open-air, open-water, and air-heated. The RO syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…While RO desalination systems have been extensively studied for their effectiveness in producing clean drinking water [13], alternative technologies like multi-effect distillation (MED) have also earned attention. Studies exploring the application of MED in water treatment have shown promising results.…”
Section: Related Workmentioning
confidence: 99%
“…While RO desalination systems have been extensively studied for their effectiveness in producing clean drinking water [13], alternative technologies like multi-effect distillation (MED) have also earned attention. Studies exploring the application of MED in water treatment have shown promising results.…”
Section: Related Workmentioning
confidence: 99%